Increased mean platelet volume is associated with acute myocardial infarction in patients with diabetes mellitus type 2 - Dervisevic, Emina; Jogunčić, Anes; Dervišević, Muamer; Salihbegović, Adis; Vukas, Haris; Kadić-Vukas, Samra; Prasko, Subhija; Krupić, Ferid (International Journal of Research in Medical Sciences, 2022)
Background: The correlation between diabetes mellitus and acute myocardial infarction is greater every day. The mean platelet volume (MPV), which is the determinant of platelet function, is an independent risk factor for the cardiovascular disease. The aim of the study was to investigate the effect of each disease (hypothyroidism, hypertension, myocardial infarction) individually and combined on MPV in diabetic patients. Methods: The cross-sectional study included 102 patients who suffer from diabetes mellitus type 2 (DMT2), of both sexes (46 females, 56 males), with the average age of 58.91 (SD=12.93). All the patients were treated at the Primary Health Centre in Zenica from May to July 2017. All patients had diabetes mellitus and the disease had lasted for 10 years in both sexes. Results: Mean platelet volume was significantly higher in patients with myocardial infarction than in those without myocardial infarction. Age, sex, HbA1c, BMI, lipids and platelet count did not show any significance in either group of patients. Regression analysis showed that the prevalence of myocardial infarction had the highest predictive significance for MPV values, (predictor importance 0.49; coefficient 1.275, p<0.001). Conclusions: Mean platelet volume was significantly higher in patients with diabetes mellitus and myocardial infarction than in DM patients without myocardial infarction. Regression analysis showed correlation with acute myocardial infarction in patients with DMT2, but not with other chronic illnesses. The highest platelet volume indices were observed in patients with myocardial infarction. MPV can be used as a specific indicator in diabetic patients with myocardial infarction.